2015
DOI: 10.1097/nna.0000000000000241
|View full text |Cite
|
Sign up to set email alerts
|

Major Predictors of Inpatient Falls

Abstract: Findings suggest that assessments of fall risk should heavily weigh the 3 predictors identified in this study. Another approach would be to intervene based on these predictors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 0 publications
0
18
0
2
Order By: Relevance
“…The new AORN “Guideline for safe patient handling and movement” recommends that the perioperative RN evaluate the patient's risk for falling during his or her preoperative assessment as part of a health care organization's fall‐reduction program 1 . A fall risk assessment is an evaluation to identify the patient's personal and environmental risks for falling, which is an important step in preventing patient falls 2,3 . If the patient has been admitted before surgery, the fall risk assessment should already be part of the patient's medical record and available for review by the perioperative team.…”
Section: Fall Risk Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The new AORN “Guideline for safe patient handling and movement” recommends that the perioperative RN evaluate the patient's risk for falling during his or her preoperative assessment as part of a health care organization's fall‐reduction program 1 . A fall risk assessment is an evaluation to identify the patient's personal and environmental risks for falling, which is an important step in preventing patient falls 2,3 . If the patient has been admitted before surgery, the fall risk assessment should already be part of the patient's medical record and available for review by the perioperative team.…”
Section: Fall Risk Assessmentsmentioning
confidence: 99%
“… age, 8,10 history of previous falls, 2,3,5,8,11 medication use (eg, preoperative sedatives), 3,5,8,12 level of consciousness (eg, alert, lethargic), 2,3,10 ability to follow directions (eg, cognitive impairment, language barrier), 3,11‐13 sensory impairments (eg, vision, 8 hearing), 13 physical limitations (eg, spinal deformities), 13 level of coordination or balance, 3,10,13 ability to move independently (eg, limb weakness, amount of assistance required), 11,13 toileting needs (eg, incontinence, frequency, need for assistance), 2,3,11 and presence of external devices (eg, catheters, drains) 8,10 …”
Section: Fall Risk Assessmentsmentioning
confidence: 99%
“…A fall‐risk assessment is an evaluation to identify the patient's risks for falling (Sidebar 1). Contraindications for walking to the OR include a history of previous falls, a language barrier, impaired vision or hearing, and lethargy. Additional considerations and contraindications include a patient who has been premedicated, has received preoperative dilating ophthalmic drops, has undergone a regional anesthesia block, prefers not to walk to the OR, or has modesty concerns.…”
Section: Walking Patients To the Ormentioning
confidence: 99%
“…Older age, history of recent falls, impaired mobility, urinary incontinence, use of certain medications, dementia or confusion, and postural hypotension increase the risk of falling for hospitalized patients. 5 A retrospective analysis of 190 postoperative falls (i.e., within 30 days after an operation) at a Veteran's Affairs Medical Center revealed that delirium, disability, and patient transfers were the most frequent patient-related causes of falls. 6 Preoperative factors significantly associated with the incidence of falls included older age, functional dependence, physical status of class 3 or greater according to the American Society of Anesthesiologists' scale, and the need for an emergency surgery.…”
Section: Assessing Patients' Fall Riskmentioning
confidence: 99%
“…7 Patients with chronic underlying conditions may also be on medications that increase the likelihood of a fall; for example, patients taking diuretics or laxatives will need to use the restroom more frequently, and may attempt to do so without assistance. 5 Perioperative RNs transferring a patient to another unit should clearly communicate the patient's medications to other care personnel so they can recognize and acknowledge the patient's fall risk. 8 A variety of environmental factors can also increase the risk of patient falls.…”
Section: Assessing Patients' Fall Riskmentioning
confidence: 99%